2017
DOI: 10.15446/rsap.v19n6.60503
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome metabólico y actividad física en adultos mayores de la sierra ecuatoriana

Abstract: Older adults diagnosed with metabolic syndrome presented the same level of physical activity as individuals without this diagnosis. It is necessary to confirm the present findings using direct measurement instruments of physical activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
2
0
0
1
Order By: Relevance
“…However, study enrolled speci cally elderly, found that older adults with MetS presented the same level of physical activity as individuals without this diagnosis [27]. Similarly, data in our study exhibited no statistically signi cant relationship between physical activity and MetS among rural elderly.…”
Section: Discussionsupporting
confidence: 44%
“…However, study enrolled speci cally elderly, found that older adults with MetS presented the same level of physical activity as individuals without this diagnosis [27]. Similarly, data in our study exhibited no statistically signi cant relationship between physical activity and MetS among rural elderly.…”
Section: Discussionsupporting
confidence: 44%
“…Therefore they claimed that there was need for prevention strategies involving promotion of physical activity. However, study enrolled speci cally elderly, found that older adults with MetS presented the same level of physical activity as individuals without this diagnosis [27]. Similarly, data in our study exhibited no statistically signi cant relationship between physical activity and MetS among rural elderly.…”
Section: Discussionsupporting
confidence: 44%
“…Ao nível internacional estudos revelam também prevalência elevada de SM em diferentes faixas etárias, com predominância significativa no sexo feminino, em indivíduos com obesidade, e com idades maiores de 50 anos (Chimbo-Yunga et al, 2017;Jmal et al, 2019;Marbou & Kuete, 2019;Quiroz et al, 2018).…”
Section: Introductionunclassified